2016
DOI: 10.1038/srep26602
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Potent in Vitro and in Vivo Anticancer Agents Based on 1-(3′,4′,5′-Trimethoxyphenyl)-2-Aryl-1H-Imidazole

Abstract: A novel series of tubulin polymerization inhibitors, based on the 1-(3′,4′,5′-trimethoxyphenyl)-2-aryl-1H-imidazole scaffold and designed as cis-restricted combretastatin A-4 analogues, was synthesized with the goal of evaluating the effects of various patterns of substitution on the phenyl at the 2-position of the imidazole ring on biological activity. A chloro and ethoxy group at the meta- and para-positions, respectively, produced the most active compound in the series (4o), with IC50 values of 0.4-3.8 nM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
3
21
0
1
Order By: Relevance
“…In vivo studies on a mouse model also demonstrated the potential of 8 for further preclinical evaluation. 25 In an earlier report, 1,2,5-selenadiazole was incorporated in CA-4 in place of the olefinic bond; the analogue 9 exhibited potent activity on the nanomolar level in three cancer cell lines and its mechanistic action was similar to that of CA-4. 26 Xu and coworkers reported substituted 1,5-diaryl pyrazoles as CA-4 analogues with significant antiproliferative and tubulin inhibition properties.…”
Section: Recent Developments In Ca-4 Based Analoguesmentioning
confidence: 96%
“…In vivo studies on a mouse model also demonstrated the potential of 8 for further preclinical evaluation. 25 In an earlier report, 1,2,5-selenadiazole was incorporated in CA-4 in place of the olefinic bond; the analogue 9 exhibited potent activity on the nanomolar level in three cancer cell lines and its mechanistic action was similar to that of CA-4. 26 Xu and coworkers reported substituted 1,5-diaryl pyrazoles as CA-4 analogues with significant antiproliferative and tubulin inhibition properties.…”
Section: Recent Developments In Ca-4 Based Analoguesmentioning
confidence: 96%
“…Romagnoli et al [ 37 ] developed 2-substituted-1-(3,4,5-trimethoxyphenyl)-1H-imidazole (Scheme 17 ) and evaluated for anticancer activity against different cancer cell lines such as HeLa, HT-29, A549, MCF-7, Jurkat, and HL-60 using C-A4 as a reference standard. Compounds 28k, 28n , and 28o showed maximum cytotoxicity as compared to others.…”
Section: Main Textmentioning
confidence: 99%
“…To evaluate its antitumor effect in vivo, 6g was administered by the intraperitoneal route every other day, starting at day 9, at two different doses (3.0 and 7.5 mg/kg) in an allograft tumor model developed in mice. 50,51 As reference compound, CA-4P was used at 30 mg/kg. This model consists of the use of B16 murine melanoma cells that are injected in the flank of individual mice.…”
Section: Effectsmentioning
confidence: 99%